Bioethanol production through dilute sulfuric acid hydrolysis and yeast fermentation of waste paper. - Eugenio, Marcelita Nolledo
In this study, unprinted waste papers were subjected to hydrolysis using 2 percent sulfuric acid at a temperature of 121 degrees centigrade and under 15 psi pressure for 15 minutes. The sugars present in the hydrolysates were fermented with the aid of Saccharomyces cerevisiae producing ethanol which was separated through simple distillation. The amount of sugars obtained through the hydrolysis process was determined using the anthrone method. The ethanol content was assayed by determining the refractive indices of the distillates. Among the hydrolysates and distillates obtained, the waste paper with the lowest volume of 2 percent (v/v) H2SO4 used has the greatest yields of sugar (0.7697 +- 0.0062 mg) and ethanol (2.19 +- 0.03 percent). The hdrolysis process employed was not effective to break down all the cellulose and hemicellulose components of the waste paper into their respective sugar units. One-Way Analysis of Variance (ANOVA) at 95 percent confidence interval revealed a significant difference among the amounts of sugar and ethanol obtained.